2016
DOI: 10.1002/ffj.3363
|View full text |Cite
|
Sign up to set email alerts
|

Does the host tree exert any influence on the aromatic composition of the black truffle (Tuber melanosporum)?

Abstract: This work examines whether the host tree influences the aroma of Tuber melanosporum truffles. Samples were gathered in the same place (Teruel, Spain) and on the same day from four host trees: hazel, Portuguese oak, kermes oak and holm oak. The truffles were subjected to sensory and chemical analysis. The sensory analysis comprised two stages. The first was based on a sorting task while the second consisted of a descriptive analysis of the samples selected from the first test. The chemical analysis examined the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…This conclusion also had many similarities with other related Chinese truffle aroma studies [15,26]. The unique aroma of Chinese truffles might also be related to the plant environment, soil conditions, such as host tree and complex bacterial colonies in soils [36,37]. GC-O sensory evaluation combined with OAVs could provide a better assessment of key aroma compounds.…”
Section: Resultssupporting
confidence: 76%
“…This conclusion also had many similarities with other related Chinese truffle aroma studies [15,26]. The unique aroma of Chinese truffles might also be related to the plant environment, soil conditions, such as host tree and complex bacterial colonies in soils [36,37]. GC-O sensory evaluation combined with OAVs could provide a better assessment of key aroma compounds.…”
Section: Resultssupporting
confidence: 76%
“…As such, volatile and bacterial community data between the truffle fruiting bodies, even within a single site, largely varied. It is possible that host trees in association with the truffles were a source of the wide variation seen in the current study, as previously suggested for T. melanosporum (Culleré et al ., 2017). In the current study, the host trees were not provided by truffle hunters.…”
Section: Discussionmentioning
confidence: 99%
“…There was an inherently large amount of variation in volatile and microbiome data between the fruiting bodies of the truffles even within a single site. It is possible that host trees in association with the truffles was a source of the wide variation seen in the current study, as previously suggested for T. melanosporum (Culleré et al, 2017). In the current study, the host trees were not provided by truffle hunters, as to the best of our knowledge, T. magnatum fruiting bodies were all wild, which may have added to variability.…”
Section: What Could Be the Drivers Of Volatile/aroma And Microbial Vamentioning
confidence: 54%